Influence of Foliar Application of Magnesium on Horticultural Crops: A Review - Muhammad Adnan; Koko Tampubolon; Fazal ur Rehman; Muhammad Sulaman Saeed; Muhammad Sikander Hayyat; Muhammad Imran; Rohoma Tahir; Jitendra Mehta (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2021)
Introduction: Magnesium is very important nutrient and performs a significant part in development and formation of many sink organs like roots and seeds. Furthermore, its fertilization significantly affects yield and numerous physiological mechanisms in different horticulture crop species. Moreover, its deficiency caused germination and reduction in horticulture crop stand. Nevertheless, its adequate concentration by foliar application plays important role in biochemical and physiological processes of plants like proteins synthesis, metabolism of carbohydrates, enzymes activation and energy transferring. Worldwide, many of our horticulture crops are facing low yield and quality problem due to fertilizer application at inadequate rate. The current review focuses on the impact of foliar applied Mg on some important cultivated horticultural crops (sugar beet, tomato, banana, potato, spinach, cauliflower, cassava, garlic, green case, potus, cucumber and grapes). Review results: Our extensive review has demonstrated that magnesium is very important factor limiting horticulture crop production but its negative impacts can be reduced by foliar application of magnesium. Foliar application of Mg can be recommended for correcting deficiencies because foliar sprays have no long term residual effect and every time fresh applications must be given to each crop. Moreover, amount depends on the nutrient status of crop and soil.